Pengaruh Kepemilikan Institusional, Likuiditas Dan Ukuran Perusahaan Terhadap Profitabilitas Dengan Struktur Modal Sebagai Variabel Intervening Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Periode 2016-2020 - Windy Oswita; Rizki Filhayati Rambe; Syamsul Bahri Arifin (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2023)
This study aims to determine the effect of institutional ownership, liquidity, firm size on profitability with capital structure as an intervening variable in manufacturing companies listed on the Indonesia Stock Exchange. This research is causal associative research and the type of data used is quantitative data. The data used is obtained from the company's financial statements that have been audited on the Indonesia Stock Exchange during the study period. The population of this study are manufacturing companies for the 2016-2020 period, which amount to 195 companies. The sample in this study amounted to 21 companies. The analytical method used was partial least square analysis with outer model analysis, inner model analysis, hypothesis testing. The results of this study indicate that partially institutional ownership, liquidity, firm size and capital structure have no effect on profitability, institutional ownership of liquidity, firm size has no effect on capital structure. Indirectly, the capital structure is not able to mediate the influence of institutional ownership, liquidity, firm size on profitability